Attuned learning : rabbinic texts on habits of the heart in learning interactions - Holzer, Elie (Boston : Academic Studies Press, 2016)
"Practice-oriented educational philosopher Elie Holzer invites readers to grow as teachers, students, or co-learners through "attuned learning," a new paradigm of mindfulness. Groundbreaking interpretations of classical rabbinic texts sharpen attention to our own mental, emotional, and physical workings as well as awareness of others within the complexities of learning interactions. Holzer integrates pedagogical pathways with ethical elements of transformative teaching and learning, the repair of educational disruptions, the role of the human visage, and the dynamics of argumentative and collaborative learning. Literary analyses reveal that deliberate self-cultivation not only leads to ethical and spiritual growth, but also offers a corrective for the pitfalls of the contemporary calculative modalities in educational thinking. The author speaks to the existential, humanizing art of learning and of teaching. This book can serve as a companion volume for A Philosophy of Havruta: Understanding and Teaching the Art of Text Study in Pairs, adding a new dimension of its model of joint learning"--Publisher's description.
Attuned acknowledgments -- Part one: Conceptual frameworks. The concept of attuned learning -- Reading rabbinic texts for education -- Part two: Co-learners attuned learning. Introduction: collaborative learning in rabbinic literature -- Self-refinement in argumentative learning -- Study partners learning -- Part three: Teachers and students attuned learning. Introduction: teaching in rabbinic literature -- Learning transformations -- Disruptions and repairs -- The visages of learning interactions -- Part four: Attuned learning and educational thought. Attuned learning in contemporary contexts -- Glossary of technical and foreign terms and language usage
Includes bibliographical references and index.
Description based on online resource; title from electronic title page (ProQuest Ebook Central, viewed February 1, 2019).
Master record variable field(s) change: 050
Keywords: Education in rabbinical literature; Learning -- Religious aspects -- Judaism; RELIGION -- Judaism -- General; Education in rabbinical literature; Electronic books